Optimizing Tissue Sampling for the Diagnosis, Subtyping, and Molecular Analysis of Lung Cancer - Ofiara, Linda Marie; Navasakulpong, Asma; Beaudoin, Stephane; Gonzalez, Anne Valerie (Frontiers in Oncology, 2014)
Lung cancer has entered the era of personalized therapy with histologic subclassification and the presence of molecular biomarkers becoming increasingly important in therapeutic algorithms. At the same time, biopsy specimens are becoming increasingly smaller as diagnostic algorithms seek to establish diagnosis and stage with the least invasive techniques. Here, we review techniques used in the diagnosis of lung cancer including bronchoscopy, ultrasound guided bronchoscopy (EBUS), transthoracic needle biopsy and thoracoscopy. In addition to discussing indications and complications, we focus our discussion on diagnostic yields and the feasibility of testing for molecular biomarkers such as EGFR and ALK, emphasizing the importance of a sufficient tumour biopsy.